Priority conservation areas for Cedrus atlantica in the Atlas Mountains, Morocco - Rachid Cheddadi; Pierre Taberlet; Frédéric Boyer; Eric Coissac; Ali Rhoujjati; Davnah Urbach; Cécile Remy; Carla Khater; Salwa elAntry; Jalila Aoujdad; Matthieu Carré; Gentile Francesco Ficetola (Conservation Science and Practice, 2022)
Abstract Assessing biodiversity loss and species extinction is necessary to warn society and raise awareness of the impacts of ongoing climate change. Prioritizing protected areas is the pragmatic and applicable management measure under the pressure of ongoing climate change and limited resources to conserve species at risk of extinction. We developed a novel conservation index (CI) to prioritize areas and populations of an endangered mountain tree species that need protection in the face of ongoing climate change, as conservation of all populations may not be realistic. This CI integrates (1) mountain topography to identify potential refugial areas with suitable microclimates, (2) genetic diversity to assess the adaptive capacity of local populations, and (3) hypothetical climate change in the species' range. We applied this CI to Atlas cedar, an endemic and threatened species whose populations are scattered throughout the Moroccan mountains. This index provided a scale for 33 populations studied and suggests that genetically diverse populations located in rugged areas where future local climate may overlap with their current climatic niche should receive a higher conservation priority. This index may also be applicable to other mountain species with scattered populations and is likely to be more accurate if more precise climate data are used at the microrefugia scale.